Managing diversity in public sector workforces - Riccucci, Norma (Boulder, Colo. Westview Press, 2002)
As we enter the twenty-first century, America?s workforce looks markedly different than it ever has before. Compared with even twenty years ago, more white women, people of color, disabled persons, new and recent immigrants, gays and lesbians, and intergenerational mixes now work in America. The way in which government employers embrace this opportunity of diversity will clearly distinguish effective and efficient organizations from those which are unproductive and unable to meet the demands and necessities of the American people in the new century.This book addresses the demographic changes to the labor force and workplace and the ways in which government employers are managing the imminently diverse populations that now fill public sector jobs. It addresses the specific management strategies and initiatives relied upon by public sector employers as well as the implications of effectively managing variegated workforces for the overall governance of American society.
Includes bibliographical references and index.
Keywords: Civil service --United States --Personnel management